SISTEM INFORMASI GEOGRAFIS PEMETAAN POTENSI PERTAMBANGAN KABUPATEN SUMBAWA - Hizbullah, Mohamad Zaky; Agustian H, sahid (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
Geographic Information System or GIS is a computer-based information system to store, manage, analyze, and retrieve geographically referenced data. By utilizing GIS, it will make it easier for users or decision makers to determine the policies taken, especially those related to spatial aspects or what is also called spatial. The purpose of this research is (i) Processing data and presenting data results using webgis with CodeIgniter and Qgis frameworks. Learning about webgis using CodeIgniter and Qgis frameworks. (ii) Building a Geographic Information System for mapping the mining potential in Sumbawa Regency based on WebGIS. The research method used is Waterfall. resulted in a Geographic Information System for Mapping the Mining Potential of Sumbawa Regency. The Mining Potential of Sumbawa Regency is 161 mines. The majority are Sand Mines with a total of 48 mines and a minority of Petroleum Mines with a total of 3 mines.